Preventing Foodborne and Non-foodborne Illness: Vibrio parahaemolyticus - Anita C. Wright; Renée M. Goodrich; Michael A. Hubbard; Keith R. Schneider (EDIS, 2016)
Vibrio parahaemolyticus is a naturally occurring bacterium that inhabits coastal brackish marine waters throughout the world and is commonly found in the United States and Canada. If ingested in sufficient numbers, this bacterium can cause illness such as gastroenteritis with symptoms such as cramps, vomiting, and nausea. Illnesses linked with this organism are usually associated with the consumption of raw or improperly cooked seafood, particularly raw oysters. This 3-page fact sheet is a major revision that discusses Vibrio parahaemolyticus, illness caused by the bacterium, factors that increase risk of infection, methods of infection, seafood and shellfish handling recommendations, and prevention. Written by Anita C. Wright, Renée M. Goodrich, Michael A. Hubbard, and Keith R. Schneider, and published by the UF Department of Food Science and Human Nutrition. Original publication date: July 2009. Revised: October 2015.